Domestic Violence Against Women in Ghana - Damenshie-Brown, R. (University of Ghana, 2013)
Domestic violence against women has been recognized globally as a major violation of a woman’s human rights. Women’s socioeconomic and demographic characteristic has made some women subject to abuse than other women. This study primarily examined women’s socioeconomic and demographic characteristics and their experience of domestic violence. The study also examined the regional differentials of domestic violence against women in Ghana. A total number of 1671 women aged 15-49 made up the study sample. The study used data from the 2008 Ghana Demographic and Health Survey. The relationship between the independent variables and the dependent variables was analyzed using bivariate techniques. Binary logistic regression was computed to examine the effect of some demographic and socio-economic characteristics of respondents and domestic violence. Findings from the study indicated that women’s characteristics (region, type of place of residence, and marital status, male dominance, and the educational status) were significant predictors of domestic violence against women at both the bivariate and binary logistic regression model. This suggests that women who are less empowered are often subject to DV. Attention should therefore be focused on encouraging women to attain higher education thereby enabling them to be more empowered. Also, further research is needed on domestic violence especially focusing on both partners characteristics. Again more qualitative research must be encouraged in this area to be able to unearth the lived experiences of women on domestic violence since this could not be shown using quantitative method.
Thesis (MA) - University of Ghana, 2013